Examining the Efficacy of Medial Meniscus Posterior Root Repair: A Meta-analysis and Systematic Review of Biomechanical and Clinical Outcomes. Issue 7 (June 2023) - Perry, Allison K.; Lavoie-Gagne, Ophelie; Knapik, Derrick M.; Maheshwer, Bhargavi; Hodakowski, Alexander; Gursoy, Safa; LaPrade, Robert F.; Chahla, Jorge
Background: Medial meniscus posterior root (MMPR) injuries accelerate the progression of osteoarthritis. While partial meniscectomy was once considered the gold standard for treatment, meniscus root repair has become increasingly utilized with reported improvements in clinical and biomechanical outcomes. Purpose: To perform a systematic review of biomechanical outcomes and a meta–analysis of clinical and radiographic outcomes after MMPR repair. Study Design: Meta-analysis and systematic review; Level of evidence, 4. Methods: The PubMed, Embase, and Cochrane databases were queried in August 2021 for studies reporting biomechanical, clinical, and radiographic outcomes after MMPR repair. Biomechanical studies were assessed for main results and conclusions. Data including study characteristics, cohort demographics, and outcomes were extracted. Included clinical studies were analyzed with a random–effects meta-analysis of proportions for binary outcomes or continuous outcomes for mean differences between preoperative and postoperative time points. Subgroup analysis for studies reporting repair outcomes with concomitant high tibial osteotomy (HTO) was performed where appropriate. Results: A total of 13 biomechanical studies were identified and reported an overall improvement in mean and peak contact pressures after MMPR repair. There were 24 clinical studies, consisting of 876 patients (877 knees), identified, with 3 studies (106 knees) reporting outcomes with concomitant HTO. The mean patient age was 57.1 years (range, 23-74 years), with a mean follow–up of 27.7 months (range, 2-64 months). Overall, clinical outcomes (Lysholm, Hospital for Special Surgery, International Knee Documentation Committee, visual analog scale for pain, Tegner, and Knee injury and Osteoarthritis Outcome Score scores) were noted to improve postoperatively compared with preoperatively, with improved Lysholm scores in patients undergoing concomitant HTO versus MMPR repair alone. Meniscal extrusion was not significantly improved after MMPR repair compared with preoperative measurements. The progression in Kellgren-Lawrence grades from grade 0 to grades 1 to 3 occurred in 5.9% (21/354) of patients after repair, with no patients progressing from grades 1 to 3 to grade 4. Conclusion: MMPR repair generally improved biomechanical outcomes and led to improved patient–reported outcomes with greater improvements noted in patients undergoing concomitant HTO. Repair did not significantly improve meniscal extrusion, while only 5.9% of patients were noted to progress to low–grade osteoarthritis. The high level of heterogeneity in the included biomechanical and clinical investigations emphasizes the need for more well–designed studies that evaluate outcomes after MMPR repair.